Transarterial chemoembolization combined with lenvatinib versus transarterial chemoembolization combined with sorafenib for unresectable hepatocellular carcinoma: A systematic review and meta-analysis - Liu, Jun-Ning; Li, Ji-Jiang; Yan, Shu; Zhang, Guang-Nian; Yi, Peng-Sheng (Frontiers in Oncology, 2023)
Background: The combination of tyrosine kinase inhibitors (TKIs) and transarterial chemoembolization (TACE) fulfills an important role in the treatment of unresectable hepatocellular carcinoma (uHCC). Among the combination therapies, both lenvatinib and sorafenib combined with TACE are recommended as first-¬line treatments for uHCC. However, at present, limited data are available concerning the efficacy and safety of these two combination therapies in uHCC. Methods: A detailed systematic search for studies on lenvatinib plus TACE (LEN+TACE) and sorafenib plus TACE (SOR+TACE) was conducted in the online databases PubMed, Embase and The Cochrane Library. The outcome data including overall survival (OS), progression free survival (PFS), time to progression (TTP), tumor response and adverse events (AEs), were independently extracted by two authors in a standardized way. Results: One randomized controlled trial and five cohort studies with 598 patients (LEN+TACE: 261, SOR+TACE: 337) were included in the meta-analysis. A higher rate of odds ratio (OR) for the objective response rate (ORR) [OR: 3.63; 95% confidence intervals (95% CI): 1.89-6.95; I squared statistic (I2) = 57%, P < 0.001] and disease control rate (DCR) (OR: 3.78; 95% CI: 2.00-7.16; I2 = 52%, P = 0.0001) were observed in the LEN+SOR group compared with the SOR+TACE group. The LEN+TACE group also had significant longer OS [hazard ratio (HR): 0.67; 95% CI: 0.52-0.85; I2 = 1%, P = 0.001], PFS (HR: 0.49; 95% CI: 0.38-0.62; I2 = 0%, P ＜ 0.001) and TTP (HR: 0.62; 95% CI: 0.45-0.84; I2 = 0%, P = 0.002) compared with the SOR+TACE group. The incidence of hypertension (OR: 3.05; 95% CI: 1.45-6.39; P = 0.003) and proteinuria (OR: 5.25; 95% CI: 1.73-15.89; P = 0.003) were significantly higher in the LEN+TACE group than SOR+TACE group, while LEN+TACE group exhibited a lower rate of hand–foot–skin reaction (HFSR) (OR: 0.51; 95% CI: 0.27-0.95; P = 0.03) compared with the SOR+TACE group. Conclusion: The combination therapy of LEN+TACE showed significant superiority compared with SOR+TACE in terms of its efficacy for patients with uHCC. SOR+TACE should be recommended as a replacement therapy when serious AEs occur during the administration of LEN+TACE as the combination therapy.